Picture Policies in Documents: Visual Display and Epistemic Practices - Lindner, Ines (Intermédialités / Intermediality, 2010)
This essay discusses the specific relationships between images and text in the journal Documents which Georges Bataille edited from 1929 to 1930. Visual display is of central importance in the publication, the images do not illustrate, they operate on the same plane as the text, and the dynamics created through their interplay are decisive. They shape the attack on scientific discourse and every kind of idealism. The journal did not survive beyond the second year, but it became a catalyst for those involved and a source of postmodern thinking through its picture policies.